Shared Syntactic Representations in Balanced Bilinguals: Cross-linguistic Priming with and without Verb Overlap. Issue 1 (2nd January 2020) - Gámez, Perla B.; Vasilyeva, Marina
ABSTRACT: This study investigated cross-linguistic priming in six-year-old, balanced Spanish-English bilinguals ( n  = 60). We examined bilinguals' production of transitive forms in English (active, passive) after exposure to Spanish transitives ( Study 1; M age = 6.2 years; SD = 0.3) and their production of transitive forms in Spanish (active, passive) after exposure to English transitives ( Study 2; M age = 5.9 years; SD = 0.5). We varied whether the verb matched between the modeled prime sentences and target drawings that children described. Results revealed two-way, cross-linguistic structural priming effects, from Spanish to English as well as English to Spanish. Further, the results did not show evidence of a lexical boost in priming. These findings suggest that by school age, balanced bilingual children have generalized, shared syntactic representations and that language experience may influence the strength of the connections between these syntactic representations and lexical items.